MANAJEMEN KURIKULUM SEKOLAH ISLAM (Studi Kasus Sekolah Dasar Islam Terpadu Sekolah Unggulan Islami (SUIS) Bogor) - Ade Wahidin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
AbstractThis study aims to determine the extent to which the theory of management according to William Spriegel which includes Planing, Organizing, Controlling or abbreviated POC harmoniously applicable to the management of Islamic Primary School Unified Islamic School (SUIS) Bogor.The research was conducted with qualitative inductive methodology, and the main subjects were Headmaster, Deputy Head of Curriculum and teacher/ homeroom teacher. The data were collected through observation and interviews and document analysis.The result of the research proves that POC theory is aligned with the management of SD IT SUIS in curriculum aspect. But not completely aligned in aspects of Human Resources, Facilities And Infrastructure, and Financing.Keywords: Management, Islamic SchoolAbstrakPenelitian ini bertujuan untuk mengetahui sejauh mana teori manajemen menurut William Spriegel yang mencakup Planing (perencanaan), Organizing (pengorganisasian), Controlling (pengendalian) atau disingkat POC selaras secara aplikatif dengan manajemen Sekolah Dasar Islam Terpadu Sekolah Unggulan Islami (SUIS) Bogor.Penelitian dilakukan dengan metodologi kualitatif induktif, dan yang menjadi subjek utama adalah Kepala Sekolah, Wakil Kepala bidang Kurikulum dan guru/wali kelas. Data itu dikumpulkan melalui observasi dan wawancara serta analisis dokumen.Hasil penelitian membuktikan bahwa teori POC selaras dengan manajemen SD IT SUIS dalam aspek Kurikulum. Akan tetapi tidak sepenuhnya selaras dalam aspek Sumber Daya Manusia, Sarpras, dan Pembiayaan.